Data Mining in Cloud Computing: Survey - Rambabu M.; Gupta S.; Singh R.S. (My University, 2025)
Data and information or knowledge have been playing an essential role to understand the human day to day activities. Data mining is the process of discovering knowledge in data from various contexts and summarising useful patterns. Because of certain limitations with traditional ICT infrastructure, businesses are finding cloud computing is the powerful and cost-effective solution. Cloud computing allows the integration of data mining techniques and methods, which deals with the massive amounts of data. Cloud data mining extracts “structured” information from different Web-based data sources. Web data may be semi-structured data or unstructured data. Data mining applications in cloud computing such as classification techniques, clustering techniques, and association rule mining techniques discussed in this work. Security and privacy are one of the major challenging issues in cloud computing. Some data mining techniques such as classification algorithms discussed to classify the DoSs in cloud computing environment. © 2021, Springer Nature Singapore Pte Ltd.